COMPARISON OF Eucalypt, Pine, AND SUGARCANE CELLULOSE FIBERS USED FOR PAPER PRODUCTION - Paula, Isabela de; Guerta, Adelsimara Ceballos [UNESP]; Martinez, Renata Miliani (Univ Federal Vicosa, 2019)
Sugarcane bagasse, a waste material generated by the sugar-alcohol industry, is rich in lignocellulosic components such as cellulose and hemicellulose. The bagasse can be employed as a raw material in the pulp and paper industry, but is currently rarely used for this purpose, due to the availability of traditional sources such as Eucalyptus and Pinus. The objective of this work was to compare the physical and mechanical properties of papers produced using the cellulose extracted from sugarcane, Eucalyptus, and Pinus by the Kraft method. Four paper samples were produced using cellulose obtained from the following fiber sources: (I) 100% sugarcane bagasse; (II) 100% Eucalyptus; (III) 75% Eucalyptus + 25% Pinus; (IV) 75% sugarcane bagasse + 25% Pinus. Physical and mechanical tests were performed based on regulatory methodologies of the paper industry. The results indicated that the physical and mechanical characteristics of the paper produced from the sugarcane cellulose were similar to those of the traditional paper produced using Eucalyptus. Particular features such as good tearing resistance and tensile strength, as well as increased porosity and moisture, could be adjusted according to the intended use of the paper. Therefore, sugarcane bagasse can be considered a sustainable alternative to Eucalyptus and Pinus for the production of high quality paper, adding value to this agricultural residue.
Keywords: Lignocellulosic material; Paper sector; Kraft method